Programmable multiplier circuit designed for quantum-dot cellular automata devices. (2021) - Teen, Y.P. Arul; Subha, M.; Shabeer, Shahul Hameed; Rajesh, K.B.
Abstract: Quantum-dot Cellular Automata (QCA) is a new model at Nano-scale for conceivable replacement of conventional Complementary Metal–Oxide–Semiconductor (CMOS) technology. It is the transistor less computation approach and feasible contestant for "Beyond CMOS" device technology. This paper presents the redesigning of arithmetic logic, in particularly the possible implementation of multiplier circuits using Quantum-dot Cellular Automata. The three-way majority gate and an inverter are the basic QCA elements. The mapping of logical circuits to their QCA equivalents via direct replacement of AND and OR gates with partially utilized majority gates (i.e., with a '0' and '1' input, respectively) leads to use of QCA basic components. In this paper, we propose a programmable QCA decimal multiplier that is composed of fully utilized majority gates. The proposed circuit designed and tested by QCA Designer.